RIWAYAT PENGGUNAAN ALAT KONTRASEPSI PADA WANITA MENOPAUSE - Budi Astyandini; Rozikhan Rozikhan; Titi Mursiti (Midwifery Care Journal, 2020)
A woman's reproductive cycle begins at menarche and ends with menopause. Various factors affect a person's age at menopause.  The purpose of this study was to find out the fun of using contraception and the age of menopause that occurred in PERIP administrators in Kendal district. research  methods with observational  analytics with a retrospective approach. The population in the study was 60 people in the management of  PERIP with a total sample of 40 people selected by random sampling, primary data collection using instruments using a questionnaire filled directly by respondents, research results obtained 55% of respondents using non hormonal contraceptives especially IUDs and menopause age 70% occurred after age 55 years. The results of the study concluded that most of the non-hormonal contraception methods of menopause were mostly above 55 years. It is recommended for further research to intervene in early menopausal women and test the relationship between variables.